The social representations of employees of a long-stay institution in the interior of Minas Gerais regarding violence - Alcione Tavora Kullok; Ivana de Cássia Baptista dos Santos (Faculdade de Medicina de Botucatu (Unesp), 2010)
Brazil is going through a fast and intense process of population aging. It is estimated that 1% of elderly Brazilians are institutionalized. Despite investigative advances within the field of geriatrics and gerontology over the last decade, studies on long-stay institutions in this country are at an incipient stage and serious problems relating to quality of care are appearing. Through a qualitative, exploratory and descriptive approach, this paper investigates the social representations of employees of a long-stay institution in a municipality in the State of Minas Gerais, regarding violence at that institution. The data, from the interview transcript, were processed using content analysis. The interviewees made mention of violence and told of their sincere and deep experiences as victims. However, with regard to the elderly people, it was as if the violence always happened outside the walls, i.e. never inside the institution. Sometimes a veiled but undisclosed complaint was perceived.